Transcriptomic response of the intertidal limpet Patella vulgata to temperature extremes. (October 2021) - Moreira, Catarina; Stillman, Jonathon H.; Lima, Fernando P.; Xavier, Raquel; Seabra, Rui; Gomes, Filipa; Veríssimo, Ana; Silva, Sofia Marques
Abstract: Global warming is challenging wild species in land and water. In the intertidal zone, species are already living at their thermal limits, being vulnerable even to small increases in maximum habitat temperatures. Knowledge of the mechanisms by which many intertidal zone species cope with elevated temperatures is limited. We analysed the molecular thermal stress response of the limpet Patella vulgata under slight and frequent (one-day), and extreme and rare (three-day) warming events. Using RNA-seq to assess differential gene expression among treatments, differing molecular responses were obtained in the two treatments, with more changes in gene expression after the three-day event; with one-third of the differentially expressed transcripts being down-regulated. However, across treatments we observed shifts in gene expression for common aspects of the heat stress response including intra-cellular communication, protein chaperoning, proteolysis and cell cycle arrest. Of the 71, 675 transcripts obtained, only 259 were differentially expressed after both heating events. From these, 218 defined the core group (i.e. genes induced by thermal stress with similar expression patterns irrespective of the magnitude of the warming event). The core group was composed of already well-studied genes in heat stress responses in intertidal organisms (e.g. heat shock proteins), but also genes from less explored metabolic pathways, e.g. the ubiquitin system, which were also fundamental regardless of the magnitude of the imposed warming. Moreover, we have also identified 41 signaling genes (i.e. a set of genes responding to both events and with expression patterns specific to the intensity of thermal stress), principally including genes involved in the maintenance of extracellular structure that have previously not been identified as part of the response to thermal stress in intertidal zone organisms. These signaling genes will be useful heat stress molecular biomarkers for monitoring heat stress in natural populations. Highlights: Intertidal species already live at their thermal limits, so global warming is a threat. Single-day moderate heat (up to 30 °C) triggers a stress response in Patella vulgata . More extreme and prolonged heat further reduces metabolism and ion regulation. More than 250 genes may comprise the baseline heat stress response in P. vulgata . Genes for maintenance of extracellular structure are heat stress molecular biomarkers.